Quality of Financial Policies and Financial System Stress - Das, Udaibir (IMF Working Papers; Working Paper ;, 2005)
In this paper, we develop multi-country indices of financial system stress and quality of financial policies and use them in regression analysis of the determinants of financial stress. We find that countries with higher quality of financial policies are better able to contain the effects of macroeconomic pressures on the overall level of stress in the financial system. They are also in a better position to ensure sustainable development of the financial system.